Escape from the ivory tower : a guide to making your science matter - Baron, Nancy, 1964- (Island Press, 2010)
To effectively reach journalists and public officials, scientists need to learn new skills and rules of engagement. No matter what your specialty, the keys to success are clear thinking, knowing what you want to say, understanding your audience, and using everyday language to get your main points across. In this practical guide to communicating science, Baron explains how to engage your audience and explain why a particular finding matters. --from publisher description.